Correlation between plasma zinc (Zn) level and nutritional status of children under five years - Dedy Koesnadi, Dedy Koesnadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
The aim of this study is to determine Zn plasma level of under five year old children (age 12-48 months) in various nutritional status according to NCEIS - WHO (1983).There were 130 under-five-year old children involved in this study. The subjects were recruited from 10 Posyandu. Clinical data such as general health, weight/age (W/A), height/age (H/A), and clinical history as well as food behaviour were collected from Posyandu. Blood sampling for determination of Zn plasma level, total protein, albumin, hemoglobin, leucocyte count, hematocrit, IgM and IgG level were collected at Puskesmas.The food consumption consisted of 16 different kind of vegetables, 10 from animals, and 3 from fruits. The interviews were done by nutritionists from Dr. Sardjito General Hospital, Yogyakarta. Zn plasma level determination was done by Atomic Absorption Spectrophotometer (AAS), Hitachi polarized. Blood examination was done at the Department of Clinical Pathology, Faculty of Medicine, Gadjah Mada University/Dr. Sardjito General Hospital, Yogyakarta.The results of the study showed that the nutritional status of the children, age 12-48 months was as follows: According to W/A nutrient index 60.3% good, 35.6% moderate, 4.1% poor, and none was bad. According to H/A nutrient index 73.0% good, 19.1% moderate, 6.4% poor, and 1.5% bad. By w/h nutrient index 71.9% good, and 28,1% poor. According to Percentile Index those were lower than Percentile 3 are W/A 41.3%, H/A 57.7%, and W/H 15% between (3-5) percentile W/A 14.2%, H/A 7.1%, and W/H 12.9%, between (5-10) percentile W/A 19.0%, H/A 7.1%, and W/H 12.9%.The mean Zn plasma level was 43.4 (SD=30.4) mcg/dL, mean Zn consumption per day was 5.2 mg. According to the health indicator 1989 under-five-year old children with good nutrient status were 53.9%. By this study according to W/A index, 60.3% was good, H/A index, 73.0%, and by W/H index, 71.9% was good.There was an increasing correlation of coefficient, r in fail nutritional status categories (r=0.134) according to W/A, r = 0.197, according to H/A, and r = 1.000 according to H/W index in the poor category, but no correlation at all between good and moderate nutritional status categories.Key words : plasma zinc level - nutritional status category - children under five year - Zn dietary consumption.